Improving Critical Thinking and Cooperation Skills Using Clear Learning Models and TTS Media in Primary School Students - Noor Adha, Nita; Cinantya, Celia; Aslamiah, Aslamiah (Journal of Elementary School Education, 2024)
The problem in this research is the low critical thinking skills and low student cooperation. This is because learning is abstract and students are used to learning individually. The aim of this research is to analyze the improvement of students' critical thinking and collaboration skills using the BENING model and TTS media. This research used classroom action research (PTK) which was carried out in 3 meetings. The subjects of this research were 13 class V students at SDN Hilir Mesjid Barito Kuala, consisting of 7 male students and 6 female students, in the second semester of the 2023/2024 academic year. The results of this research show an increase in critical thinking skills of 85%. Meanwhile, cooperation obtained 92%.